2017
DOI: 10.1016/j.ijome.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Setting an agenda for biofouling research for the marine renewable energy industry

Abstract: Abstract:Extensive marine growth on man-made structures in the ocean is commonplace, yet there has been limited discussion about the potential implications of marine growth for the wave and tidal energy industry. In response, the Environmental Interactions of Marine Renewables (EIMR) Biofouling Expert Workshop was convened. Discussions involved participants from the marine renewable energy (MRE) industry, anti-fouling industry, academic institutions and regulatory bodies. The workshop aimed to consider both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Accumulation of biofouling on energy production infrastructure can increase drag (Macleod et al, 2016;Vinagre et al, 2020), affect cathodic protection (leading to corrosion), create microenvironments that encourage microbial corrosion (Blackwood et al, 2017;Li and Ning, 2019), reduce water flow in cooling systems (Venkatesan and Murthy, 2009), compromise health and safety of operators (e.g., sharp or slippery fouling on stairs and ladders), and endanger the entire plant (Satpathy and Rajmohan, 2001). Considerable costs are associated with over-engineering to combat hydrodynamic impacts and weight loadings during SSAS development as well as the requirements for extensive inspection and ongoing post-deployment maintenance (Klijnstra et al, 2017;Loxton et al, 2017).…”
Section: Energy Productionmentioning
confidence: 99%
“…Accumulation of biofouling on energy production infrastructure can increase drag (Macleod et al, 2016;Vinagre et al, 2020), affect cathodic protection (leading to corrosion), create microenvironments that encourage microbial corrosion (Blackwood et al, 2017;Li and Ning, 2019), reduce water flow in cooling systems (Venkatesan and Murthy, 2009), compromise health and safety of operators (e.g., sharp or slippery fouling on stairs and ladders), and endanger the entire plant (Satpathy and Rajmohan, 2001). Considerable costs are associated with over-engineering to combat hydrodynamic impacts and weight loadings during SSAS development as well as the requirements for extensive inspection and ongoing post-deployment maintenance (Klijnstra et al, 2017;Loxton et al, 2017).…”
Section: Energy Productionmentioning
confidence: 99%
“…There are relatively few published studies on biofouling in this sector owing partly to the early technology readiness level of MRE devices, and to commercial sensitivities (Shields et al 2011). Furthermore, in situ studies comparing coating performance in the MRE sector are absent from peer-reviewed literature (Loxton et al 2017). MRE studies have included biofouling assessments of buoys (Langhamer et al 2009;Macleod et al 2016) and have described the role that vessels and harbours, may play in the movement of fouling species (Nall et al 2015).…”
Section: Figurementioning
confidence: 99%
“…The increased cost in most cases is a result of the excessive fuel needs, caused by a significant increase in the frictional resistance of submerged surfaces due to biofouling [20]. Loxton et al [10] reported the e ect of marine biofouling on marine renewable energy devices. They stated that biofouling can reduce the energy extraction e ciency of wave or tidal energy harvesting devices, as it can increase the e ective diameter of their components, causing an increase in drag and inertia.…”
Section: Angela Bussementioning
confidence: 99%